Warming advances top‐down control and reduces producer biomass in a freshwater plankton community. Issue 1 (13th January 2017) - Velthuis, Mandy; de Senerpont Domis, Lisette N.; Frenken, Thijs; Stephan, Susanne; Kazanjian, Garabet; Aben, Ralf; Hilt, Sabine; Kosten, Sarian; van Donk, Ellen; Van de Waal, Dedmer B.
Abstract: Global warming has been shown to affect ecosystems worldwide. Warming may, for instance, disrupt plant herbivore synchrony and bird phenology in terrestrial systems, reduce primary production in oceans, and promote toxic cyanobacterial blooms in freshwater lakes. Responses of communities will not only depend on direct species‐specific temperature effects, but also on indirect effects related to bottom‐up and top‐down processes. Here, we investigated the impact of warming on freshwater phytoplankton community dynamics, and assessed the relative contribution of nutrient availability, fungal parasitism, and grazing therein. For this purpose, we performed an indoor mesocosm experiment following seasonal temperature dynamics of temperate lakes and a warmed (+4°C) scenario from early spring to late summer. We assessed phytoplankton biomass, C:N:P stoichiometry and community composition, dissolved nutrient availabilities, fungal parasite (i.e., chytrid) prevalence, and zooplankton abundance. Warming led to an overall reduction in phytoplankton biomass as well as lower C:P and N:P ratios, while phytoplankton community composition remained largely unaltered. Warming resulted in an earlier termination of the diatom spring bloom, and an epidemic of its fungal parasite ended earlier as well. Furthermore, warming advanced zooplankton phenology, leading to an earlier top‐down control on phytoplankton in the period after the spring bloom. Linear model analysis showed that most of the observed variance in phytoplankton biomass was related to seasonal temperature dynamics in combination with zooplankton abundance. Our findings showed that warming advanced grazer phenology and reduced phytoplankton biomass, thereby demonstrating how bottom‐up and top‐down related processes may shape future phytoplankton dynamics.